Understanding the dynamics and management of organic nutrient sources in smallholder farming systems: an interdisciplinary approach - Magonziwa, Blessing, author; Fonte, Steven, advisor; Davis, Jessica, committee member; Carolan, Michael, committee member; Paustian, Keith, committee member (Colorado State University. Libraries, 2021)
Smallholder farmers often face challenges in managing soil fertility due to limited inputs and high spatial variability on their farms. In many places, soil fertility, and overall soil health, is on the decline, and management of organic nutrient sources (ONS) can play a vital role in sustaining the productivity of soils. However, in mixed smallholder crop-livestock systems there is often competition for crop residues between retaining residues within fields versus feeding them to livestock. Understanding how ONS produced on-farm are managed, and the flows and drivers of this essential resource is critical for the restoration and sustainable management of soil fertility and health in smallholder agroecosystems. The objectives of this study were to: i) validate a soil health tool kit developed to facilitate smallholder research and management involving the use of ONS and other soil management strategies; ii) evaluate how different maize-based ONS (shoot, roots, manure) influence soil organic carbon (SOC) dynamics; iii) understand socio-cultural, economic, and environmental drivers of ONS allocation and use; and iv) understand management and environmental drivers SOC and nutrient (N, P and K) balances across various management scenarios. To address these objectives, a soil health tool kit to provide in-field quantitative data that are comparable to formal laboratory methods was assembled. I then validated methods used in this tool kit against standard analyses conducted at national laboratories on soils collected from 36 smallholder farms in Kenya and 115 farms in Peru. My results showed that permanganate oxidizable C and pH measured with the tool kit from Kenyan and Peruvian soils were highly correlated to the same variables measured by a standard laboratory. The tool kit and standard laboratory measures of available P were less well correlated, but also showed a significant positive relationship. Both tool kit and standard lab analyses displayed similar abilities to predict maize grain yield in Kenya. My findings suggest that the tool kit methods proposed in this study have broad applicability to smallholder farms for explaining variability in crop yields, assessing soil properties of different plots and quantifying management-induced changes in soil health. In the next study, I used a mesocosm experiment and a 13C natural abundance approach, where organic residues (maize shoots, ex-situ maize roots, in-situ maize roots and cattle manure) were incubated for 11 months to trace maize-derived C into different SOC pools. My findings indicated that there was greater stabilization of shoot-derived C (2 X more than manure and 1.6 X more than ex-situ root C) in the mineral-associated organic matter fraction. At the same time, mineral additions of N, P and S (aimed at adjusting the stochiometry of the added residue inputs) led to a 60% decrease in C stabilization in the mineral-associated fraction, compared to a control with no nutrient additions. My study highlights the potential importance of residue retention as a strategy to maintain SOC and therefore soil health and did not support the idea that strategic N, P, and S additions can facilitate C stabilization in soil over the long-term. I then used focus group discussions and conducted a survey of 184 farming households to understand socio-economic, socio-cultural, and environmental drivers of ONS allocation and use at farm scale in three contrasting agroecological zones of western Kenya. I found that the more resource endowed a farmer is, the more ONS are allocated to the main production plot within a farm. However, beyond resource endowment I observed that agroecological location, and tenure, perceived soil fertility, gender and social connections also had important influences on ONS allocation. Lastly, I examined case studies from three representative farm types within three agroecological zones in western Kenya and used a modelling approach to estimate nutrient and C flows in and out of fields. Based on the estimated flows, I then examined different scenarios representing alternative possibilities for ONS management in the region. I noted differences in inputs and allocation between the three zones, but these did not affect the overall balances, which were largely influenced by fertilizer inputs, as well as nutrient export in harvest and soil erosion. Overall nutrient balances were variable, but largely negative across the zones, farm types and field types. When exploring the different management scenarios, reducing erosion led to significantly less negative N balances in all locations. A full residue retention scenario indicated the greatest impact on K balances, while for SOC scenarios with full residue retention and lablab (a high biomass legume) incorporation resulted in at least 50 % more SOC compared to current practices. Scenarios indicate that retaining residues as well as implementing erosion control measures have the potential to effectively reduce nutrient losses as well as improve SOC stocks and that these practices should be encouraged. As research and development organizations continue to engage with smallholder farmers to reduce the burden of global food insecurity, the insights gained by this research will allow for better anticipation of drivers and obstacles to improved nutrient management in these farming landscapes and communities.
Keywords: organic nutrient sources; soil carbon modelling; soil tool kit; soil carbon dynamics; nutrient balances; soil health